Youth Space Development in Urban Kampong of Pondok Cina, Depok City, Indonesia - Putri, Nola Amallia; Mahmudi, Naswa Asyfa; Vevia, Yona Litha; Satria, Widi Dwi; Asriana, Nova (Poltekkes Kemenkes Tanjung Karang, 2024)
Youth spaces are necessary for adolescents to express themselves, build community, and strengthen identity. The study aims to identify needs and preferences and obtain alternatives for developing youth spaces in the urban kampong of Pondok Cina, Depok City. Qualitative research was conducted from February to April 2024. Data was collected through observation, in-depth interviews, and Focus Group Discussions. The study found that adolescents need multifunctional youth spaces, including places to socialize, develop talents, and exercise. An attractive, comfortable, and inclusive space design is essential, including complete facilities that support young people's activities. This study also emphasizes integrating youth spaces with environmental health, such as waste management and environmental education. Developing youth spaces that are managed effectively, sustainably, and integrated with environmental healthh can improve quality of life, prevent juvenile delinquency, and build a healthy community.